The modern poets - ibn al-Muʿtazz, ʿAbd Allāh. (Leiden)
xiv, 698 sayfa
Keywords: “The Modern Poets is the first complete translation into any language of an important and entertaining anthology compiled by the famous Arabic poet and Abbasid prince, 'Abd Allah ibn al-Mu'tazz, who reigned as Caliph in Baghdad for one day in AD 908, before being killed the next day. It contains sections on 132 8th- and 9th-century Arabic poets, famous and obscure ones, quoting poems of many kinds: praise poems, love poems, wine poems, elegies, vicious lampoons, and jesting epigrams, with many anecdotes. The translation is richly annotated, preceded by an introduction, and provided with indexes. The book offers access to a central text in Arabic literary history and a compelling window into early Abbasid culture“ --